Modelling Economic Growth Function in Nigeria: An ARDL Approach - Okafor, Chinwuba; Shaibu, Ibrahim (Asian Journal of Economics and Empirical Research, 2016)
The objectives of the study were to identify the significant variables that underlie economic growth in Nigeria, ascertain the stability of the economic growth model in Nigeria over the sample period, and examine the forecasting performance of the linear dynamic model. This study applies a linear dynamic model based on Pesaran et al. (2001) multivariate autoregressive distributed lag (ARDL) modelling technique to analyze the short-run and long-run dynamics of economic growth in Nigeria over the sample period between 1986 and 2013 using quarterly data. The empirical results show that economic growth in Nigeria finds explanation in adaptive expectations. The main determining variables of economic growth in Nigeria in the short-run and long-run are expected economic growth, population and trade openness. To achieve sustainable economic growth, it is suggested that government policies directed at improving the performance of the economy should largely consider the short-run and long-run behaviour of these variables and the policies should be pursued with high degree of transparency.